An analysis of the response to corporate unbundling announcements on the Johannesburg Stock Exchange - Jordan, Jared Bayman (My University, 2012)
This research report examines the effect of the announcement of corporate unbundling by South African corporations listed on the Johannesburg Stock Exchange. This research was carried out in order to update the literature and to analyse whether results confirm the previous research performed by Blount and Davidson (1996) or coincides with international trends, which displayed positive responses to unbundling announcements. The event study methodology was used for analysing the market’s reactions to corporate unbundling announcements. Abnormal returns were calculated using the market model approach with an event window of ten days and an estimation window of 120 days. A sample of 27 corporations were analysed in this research report during the period January 2002 to June 2011. The results indicated strong negative abnormal returns as a result of the corporate unbundling announcements. This finding confirms Blount and Davidson’s (1996) earlier research.
Keywords: Corporate unbundling; Johannesburg Stock Exchange; Shares; Prices